Custo-efetividade de opções reabilitadoras fixas para reposição de um único dente - Medeiros Neto, Manuel Henrique de (2019)
Rehabilitation options for single-tooth replacement are many and often results in a doubt for clinicians and patients. These options range from removable, tooth-fixed or implant-supported dentures. In addition, it is important to highlight that 28.3% of the Brazilian population uses some type of prosthesis. Therefore, it is necessary to discuss the cost-effectiveness of different rehabilitation options. The scientific literature is very scarce regarding economic evaluartions in Dentistry, which could subsidiary in the decision making of managers, professional and patients. This study aimed to compare the cost-effectiveness of rehabilitation options with dental implant and crown (I+C) and fixed partial denture (FPD). A systematic review was conducted to identify the costs (expressed in US $) and effectiveness (expressed in satisfaction, survival success and impact on quality of life) of both treatments. Bibliographic searches sent 1447 records, and 19 articles were selected to collect cost and effectiveness data. Markov economic models (Monte Carlo Simulation) simulated hypothetical 15-year cohorts with 2000 patients, using cost and effectiveness data from the systematic review, under the perspective of private practice. The parameters of satisfaction, success rate and impact on quality of life were used in three independent economic evaluations. Probabilistic simulations considered the parameter variation by 20% and annual discount rate of 5%. According to the systematic review, the average costs of I+C and FPD treatments were $ 3432.23 and $ 3322.52, respectively. Compared to FPD, I+C treatment showed greater satisfaction (97% vs 81%) survival success (0.2825 vs 0.1984) and impact on quality of life (21.5 vs 20.5). The I+C treatment, compared to FPD, had the following incremental cost-effectiveness ratios (ICER): US $ 8.51/satisfaction; $ 170.88/survival success; $ 132.78/quality of life. Both I+C and PPF rehabilitation options are cost-effective. I+C rehabilitation has higher cost and greater effectiveness, being the recommended option of choice in view of the greater willingness to pay and absence of patient‟s contraindication.